2017
DOI: 10.1175/bams-d-15-00276.1
|View full text |Cite
|
Sign up to set email alerts
|

A Situation-Based Analysis of Flash Flood Fatalities in the United States

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 34 publications
5
79
0
Order By: Relevance
“…The integration of individual decisions and coping capacities enables us to shift from exposure measurement to social vulnerability quantification (Terti et al, 2015). To advance in this direction, the use of welldescribed, geolocalized, time-stamped and reliable human impact datasets is needed for model verification (Terti et al, 2017).…”
Section: Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…The integration of individual decisions and coping capacities enables us to shift from exposure measurement to social vulnerability quantification (Terti et al, 2015). To advance in this direction, the use of welldescribed, geolocalized, time-stamped and reliable human impact datasets is needed for model verification (Terti et al, 2017).…”
Section: Variablesmentioning
confidence: 99%
“…Therefore, several vehicle-related accidents occur during flash floods. Death circumstances investigations showed that in postindustrial countries over half of flood victims are motorists trapped by road flooding (Ashley and Ashley, 2007;Sharif et al, 2012;Terti et al, 2017). Hence, daily mobility is pointed out as one of the primary causes of population exposure and vulnerability to flash floods (Ruin, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hourly precipitation extremes have received much attention due to the hazards they pose to human lives and infrastructure (Ashley and Ashley 2008;Terti et al 2017). Widespread increases in the magnitude of hourly precipitation extremes have been documented in the United States (US) over the past half-century ) and climate projections suggest a continued intensification of short-duration precipitation extremes with anthropogenic climate change (Prein et al 2016;Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another example is Boulder, Colorado on 12 September 2013, where the absolute record of 1-day precipitation accumulation coincided with a COL. In view of these examples, it is of interest to quantify the contribution of these organized midlatitude systems to hourly precipitation extremes, given the importance of this timescale to storm impacts (Terti et al 2017).…”
Section: Introductionmentioning
confidence: 99%